2007
DOI: 10.1080/08111140701541180
|View full text |Cite
|
Sign up to set email alerts
|

Housing Factors in Welfare Migration to and from Metropolitan Cities in Australia

Abstract: This article ascertains dimensions of welfare migration to and from two large Australian cities (Sydney and Adelaide) and persons' motivations and perceptions of well-being after moving. Housing costs were crucial in out-movement from metropolitan areas, particularly Sydney. The desire to obtain work and to be closer to family members was important for an appreciable proportion of metropolitan-ward movers. Respondents were not turnover migrants since a strong majority had lived in their origin community for ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…While counterurbanisation has been attributed as having a positive effect on reviving previously dying rural housing markets, a number of other studies have found cause for concern regarding the impact of this type of mobility and rural housing. For instance, in Australia and the United States the ability to access affordable social and private forms of housing in rural locations has been argued to produce a type of 'welfare-led' migration of low-income households to these areas (Fitchen, 1994(Fitchen, , 1995Nord et al, 1995;Cromartie and Nord, 1997;Hugo and Bell, 1998;Burnley et al, 2007;Costello, 2009;Monchuk et al, 2012). Such processes are argued to 'trap' lowincome households into poorly resourced locations, further isolating them from employment and other social services.…”
Section: Mobility and Rural Housingmentioning
confidence: 96%
“…While counterurbanisation has been attributed as having a positive effect on reviving previously dying rural housing markets, a number of other studies have found cause for concern regarding the impact of this type of mobility and rural housing. For instance, in Australia and the United States the ability to access affordable social and private forms of housing in rural locations has been argued to produce a type of 'welfare-led' migration of low-income households to these areas (Fitchen, 1994(Fitchen, , 1995Nord et al, 1995;Cromartie and Nord, 1997;Hugo and Bell, 1998;Burnley et al, 2007;Costello, 2009;Monchuk et al, 2012). Such processes are argued to 'trap' lowincome households into poorly resourced locations, further isolating them from employment and other social services.…”
Section: Mobility and Rural Housingmentioning
confidence: 96%
“…The growth of regional and rural centres could be driven by increased internal migration-the 'sea/tree change' movement being the most obvious (Gurran & Blakely, 2007), but also welfare migration driving low-income households from major urban centres to less expensive (and poorly equipped) coastal locations (Burnley et al, 2007). Thus, while the COAG criteria identify the links between capital cities and major regional centres as important (criterion 5), a broader productivity policy centred on population variables would do well to look beyond the boundaries of our major cities, as their growth will have significant and uneven impacts on other locations.…”
Section: Conclusion: a New Style Of Metropolitan Planning?mentioning
confidence: 99%
“…Regarding the existing literature on the relationship between internal migration and housing market dynamics, a considerable amount of research has been conducted on the importance of housing market conditions (house prices and/or housing supply) for internal migration dynamics -e.g., Zabel (2012), Molloy et al (2011), Gabriel et al (1992, for the US; Cameron et al (2006) for the UK, Burnley et al (2007) for Australia, Mulhern and Watson (2009) for Spain, Vermeulan and Van Ommeren (2009) for the Netherlands, and Cannari et al (2000) for Italy. Only a handful of papers, including Howard and Liebersohn (2019), Wang et al (2017), Stillman, and Mare (2008), and Tyrcha (2020) have investigated the impact of internal migration on house prices and/or rents.…”
Section: Literature Reviewmentioning
confidence: 99%